Islamic Fintech and Customer Experience: A Bibliometric Analysis - Ziky, Rachid; Laarj, Mohamed; Idboufakir, Abderrahim; Abriane, Ahmed (International Review of Management and Marketing, 2026)
The business sector has seen accelerated advancements in technological innovations, most notably in artificial intelligence and blockchain technologies. This transformation is likely to have a significant impact on Islamic finance and, ultimately, on the customer experience. Indeed, this article aims to examine publication trends related to Islamic FinTech and customer experience. To achieve this, we adopt a bibliometric analysis coupled with a Systematic Quantitative Literature Review (SQLR). References were collected from the Scopus database over the period from 2016 to 2025. The application of selection criteria resulted in a final dataset of 664 publications. The results reveal a substantial increase in publications, particularly from 2023 onwards. Moreover, this bibliometric analysis indicates that only a limited number of authors from South and Southeast Asia have exerted a notable influence in the field in terms of publication volume.